2022
DOI: 10.1097/spv.0000000000001261
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery Protocols in Urogynecologic and Pelvic Floor Reconstructive Surgery: A Systematic Review and Meta-Analysis

Abstract: Importance The implementation of Enhanced Recovery After Surgery (ERAS) protocols may optimize the clinical outcome of surgical patients, by reducing the length of hospital stay (LOS) and improving the quality of recovery. Objective This study aims to evaluate the impact of ERAS protocols in the intraoperative and postoperative course of patients undergoing pelvic floor reconstructive surgery. Methods A systematic search of PubMed/MEDLINE, Embase, and the Cochrane Library was conducted up to January 2022, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…As programs such as the Hospital Readmissions Reduction Program expand to POP surgery, 30-day hospital readmission will grow in importance in a pay-for-performance health care system because it serves as a surrogate marker for quality and safety. Enhanced recovery after surgery (ERAS) protocols decrease multiple-day hospital admissions, postoperative pain, and adverse events and have been successfully applied in urogynecology, 13–16 thus making same-day discharge a viable option for women undergoing POP surgery. In both single-site and large multisite studies, same-day discharge has been shown to be a safe alternative to next-day discharge (with similar readmission and ED rates) with high patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…As programs such as the Hospital Readmissions Reduction Program expand to POP surgery, 30-day hospital readmission will grow in importance in a pay-for-performance health care system because it serves as a surrogate marker for quality and safety. Enhanced recovery after surgery (ERAS) protocols decrease multiple-day hospital admissions, postoperative pain, and adverse events and have been successfully applied in urogynecology, 13–16 thus making same-day discharge a viable option for women undergoing POP surgery. In both single-site and large multisite studies, same-day discharge has been shown to be a safe alternative to next-day discharge (with similar readmission and ED rates) with high patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%